Apoptosis induction in human leukemia cell lines by gold nanoparticles synthesized using the green biosynthetic approach - Namvar, Farideh; Rahman, Heshu Sulaiman; Mohamad, Rosfarizan; Rasedee, Abdullah; Swee, Keong Yeap; Chartrand, Max Stanley; Azizi, Susan; Mohd Tahir, Paridah (Hindawi Publishing Corporation, 2015)
Gold nanoparticles were grown on Sargassum muticum water extract (S-GNPs) using the green biosynthetic approach. The nanoparticles were characterized using UV-visible spectroscopy, zeta potential, and transmission electron microscopy (TEM). The resulting S-GNPs were spherical and crystalline with a size of <10 nm. The in vitro anticancer activity was demonstrated in human leukemia cell lines. The cancer cells were treated with different concentrations of S-GNPs, and calorimetric (MTT) assay used for the cytotoxicity test, which resulted in an IC50 value of 4.22 ± 1.12, 5.71 ± 1.4, 6.55 ± 0.9, and 7.29 ± 1.7 μg/mL for each of the K562, HL-60, Jurkat, and CEM-ss cells, respectively. Thus, the K562 was selected for the next experiments. Furthermore, apoptosis induction was confirmed by Hoechst 33342, annexin V staining, and caspase-3/-9 activity tests. The cell cycle analysis exhibited a significant increase in the accumulation of S-GNPs treated cells at the sub-G1 phase, demonstrating the induction of apoptosis by S-GNPs. The nature of the inhibition of cancer cell growth by S-GNPs could open the way for further research in the design of green synthesis therapeutic agents, particularly in nanomedicine, for the treatment of cancer.